Asymptotic stability and stabilisation of uncertain delta operator systems with time‐varying delays. Issue 8 (1st May 2013) - Xie, Xiaochen; Yin, Shen; Gao, Huijun; Kaynak, Okyay
Abstract : This study focuses on the asymptotic stability and stabilisation of uncertain linear systems with time‐varying delays via delta operator approach. By employing a new model formulation, the time‐delayed delta operator system is transformed into an interconnected system for which the uncertainties can become easy to deal with. Based on a two‐term approximation of delayed state and scaled small gain theorem, new delay‐dependent sufficient conditions of robust asymptotic stability and state‐feedback stabilisation of an uncertain delta operator time‐delayed system are established by using a novel Lyapunov–Krasovskii functional. The criteria obtained unify some previously suggested relevant methods seen in literature for achieving asymptotic stability and stabilisation of both continuous and discrete systems into the delta operator framework. Numerical examples presented explicitly demonstrate the advantages and effectiveness of the proposed methods.